A lesson in valuation from Estonia: The difference between the fundamental value of equity under distributed and traditional profit taxation systems - Mark Kantšukov; Priit Sander (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
Corporate value creation and management are one of the key issues for any business enterprise. A gap exists in research into the implications of the distributed profit taxation ( DPT ) system in Estonia for corporate value creation. Under the Estonian system of corporate taxation, companies need not pay income tax on undistributed earnings, allowing them to postpone income tax liability indeterminately. This theoretical paper compares the relationship between a company's equity value and taxation of profits under traditional (or classical) ( TPT ) and DPT systems. A TPT system is a system where the amount of corporate income tax is determined by the profit the company earned during the taxation period. We show that fundamental equity value under a DPT system should be higher vis-à-vis equity value under a TPT system ( ceteris paribus ). To illustrate this, we use a dividend discount model and values from a hypothetical company. The equity value under DPT is also higher when financial leverage is considered. The results suggest that conventional valuation models and their inputs should be adjusted when valuing Estonian companies. Ignoring these adjustments runs the risk of undervaluing the equity of Estonian companies, as well as the equity of companies operating under similar tax regimes.
Keywords: C02; G12; H25; 650; equity valuation; dividend discount model; distributed profit taxation; financial leverage; theoretical finance